2017
DOI: 10.1016/j.ttbdis.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the characterization of Rickettsia species in ticks collected from humans

Abstract: Rickettsiae (family Rickettsiaceae, order Rickettsiales) are obligate intracellular bacteria transmitted by arthropod vectors. Several Rickettsia species causing vector-borne rickettsioses belong to the spotted fever group (SFG). Traditionally, Rickettsia conorii has been considered as the main etiologic agent of Mediterranean spotted fever. However, the molecular characterization of rickettsiae allowed identifying other species involved in spotted fever in the Mediterranean region. In this study, 42 ticks col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
1
26
0
3
Order By: Relevance
“…Gene reduction was demonstrated in vitro by “Spiegelman's Monster,” where a long coding phage RNA in the presence of an RNA polymerase, free nucleotides, and salts degenerated to a small extremely fast replicating ncRNA after 74 generations, demonstrating that loss of genes for the benefit of fast replication can occur . Rickettsia , mitochondria, and chloroplasts are other examples for loss of genes resulting in an exclusively intracellular lifestyle …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gene reduction was demonstrated in vitro by “Spiegelman's Monster,” where a long coding phage RNA in the presence of an RNA polymerase, free nucleotides, and salts degenerated to a small extremely fast replicating ncRNA after 74 generations, demonstrating that loss of genes for the benefit of fast replication can occur . Rickettsia , mitochondria, and chloroplasts are other examples for loss of genes resulting in an exclusively intracellular lifestyle …”
Section: Discussionmentioning
confidence: 99%
“…150,151 Rickettsia, mitochondria, and chloroplasts are other examples for loss of genes resulting in an exclusively intracellular lifestyle. 141,142,145 Possibly, viruses gave up their independence for a parasitic lifestyle. In this case, viruses could be our oldest ancestors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, H. punctata is known from many European, North African, Asian and Mediterranean countries-Palearctic realm (Estrada-Peña 2004; [1,4,5,9,11,13,16,21]. Recently, many studies in the Middle East have reported H. punctata infesting humans; for instance, Turkey [6,16], Palestine, Iraq [8], Iran [14], Sicily [3] and Israel [15]. Although H. punctata occurrence in Lebanon was lately reported by Dabaja et al [7] and on ruminants, its finding on humans (mainly remains) has not been recorded yet from this country.…”
mentioning
confidence: 99%